Two new species of the genus Igerna (Hemiptera: Cicadellidae: Megophthalminae) from India - Meshram, Naresh M.; Bose R., N.s. Chandra; Parveen, Shama (Zootaxa, 2015)
Two new megophthalmine species of leafhoppers, Igerna kolasibensis sp. nov. and I. shillongensis sp. nov., are described from India, Mizoram and Meghalaya, respectively. Detailed morphological descriptions, illustrations and photographs are provided. An updated key to the species and taxonomic notes on the genus are provided.